Jagāntīla krāntikāraka laḍhāyā : hẽ pustaka Eḍavarḍa-Krīsī hyã̄cyā "Jagantīla pandharā krāntikāraka laḍhayā" hyā pustakāce adharẽ Janārdana Sakhārāma Karandīkara hyāñnĩ̄ lihilẽ - Karandīkara, Ja. Sa. (Janārdana Sakhārāma) (SAMP early 20th-century Indian books project, 1907)
Based on the fifteen decisive battles of the world of Sir Edward Shepherd Creasy, 1812-1878.